Synthesis and Bioactivities of Novel Piperonylic Acid Derivatives Containing a Sulfonic Acid Ester Moiety - Xie, Dandan; Hu, Xin; Ren, Xiaoli; Yang, Zaiping (Frontiers in Chemistry, 2022)
The crop loss caused by bacteria has increased year by year due to the lack of effective control agents. In order to develop efficient, broad-spectrum, and structurally simple agricultural bactericide, the structure of piperonylic acid was modified and a series of novel piperonylic acid derivatives containing a sulfonic acid ester moiety was synthesized. Bioassay results indicated the compounds exhibited significantly antibacterial activities. Among them, compound 41 exhibited excellent antibacterial activities against Pseudomonas syringae pv. Actinidiae (Psa), with inhibitory value 99 and 85% at 100 μg/ml and 50 μg/ml, respectively, which was higher than that of thiodiazole-copper (84 and 77%) and bismerthiazol (96 and 78%). In addition, some compounds also showed moderate insecticidal activity against Spodoptera frugiperda. The abovementioned results confirm the broadening of the application of piperonylic acid, with reliable support for the development of novel agrochemical bactericide.